Eruption of an impacted canine in an adenomatid odontogenic tumor treated with combined orthodontic and surgical therapy - DOLANMAZ, DOĞAN; Erdur, Emire Aybuke; Ileri, Zehra; Ugurluoglu, Ceyhan; Cakir, Mustafa; Dolanmaz, DOĞAN (My University, 2016)
An adenomatoid odontogenic tumor is an uncommon asymptomatic lesion that is often misdiagnosed as a dentigerous cyst. It originates from the odontogenic epithelium. Enucleation and curettage is the usual treatment of choice. Marsupialization may be attempted instead of extraction of the impacted tooth, since it provides an opportunity for tooth eruption. This case report is the first to report on the eruption of an impacted canine in an adenomatoid odontogenic tumor treated with combined orthodontics and marsupialization. The impacted canine erupted uneventfully, with no evidence of recurrence 3 years after the treatment.